Pooled analysis of response rate and overall survival of Tyrosine Kinase inhibitor combinations in phase II clinical trials of non-small cell lung cancer - Karim, Samia Binte (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2024.